Asymmetrical Body Perception: A Possible Role for Neural Body Representations. - Linkenauger, Sally A.; Witt, Jessica K.; Bakdash, Jonathan Z.; Stefanucci, Jeanine K.; Proffitt, Dennis R. (Psychological Science., 2009)
A study examined perceived arm length among right- and left-handed people. Data were obtained from three experiments that explored handedness and perception of arm length, handedness and perceived reach, and perceived hand size and grasping ability in right-handed participants, respectively. Findings revealed that when looking at each arm and hand individually, right-handed participants perceived their right arms and right hands to be longer than their left arms and left hands. Findings also revealed that in contrast, those who are left-handed perceived both arms accurately. Findings suggested a possible association between implicit body maps in the brain and conscious perceptions of the body. Findings are discussed in detail.